Biodegradation improvement of bioinspired crosslinked and noncrosslinked polyvinyl alcohol nanocomposites with cellulose nanocrystals extracted from rice straw through natural soil burial exposure. Issue 10 (30th May 2022) - Chin, Kwok‐Mern; Sam, Sung Ting; Ong, Hui Lin; Wong, Yee Shian; Tan, Wai Kian
Abstract: Polyvinyl alcohol with different cellulose nanocrystals (CNC) content extracted from rice straw were prepared by using solution casting method and their biodegradability in natural soil burial were studied. Ethanedioic acid (EA) was introduced as a crosslinker. The synthesized noncrosslinked and crosslinked PVOH/CNC nanocomposites films and their biodegradation were characterized with Fourier transform infrared spectroscopy (FTIR), tensile test, weight loss, Field Emission Scanning Electron Microscopy (FESEM), differential scanning calorimetry (DSC). The changes in chemical properties before and after biodegradation were confirmed through FTIR. Tensile test revealed that the tensile strength and elongation at break reduced as time of soil burial increases. Morphological study showed the extent of surface deterioration before and after soil burial, where the addition of CNC displayed greater deterioration. Melting temperature and crystallinity increased with addition of CNC but decreased after crosslinking. However, melting temperature and crystallinity of all nanocomposites increased after biodegradation. PVOH degrading bacteria were isolated and identified to be Bacillus cereus strain CCM 2010 and Bacillus cereus strain ATCC 14579. Biodegradation of the bionanocomposites were concluded to be in the following decreasing order: PVOH/CNC > PVOH/EA/CNC > PVOH > PVOH/EA. Abstract : This research details on the biodegradability of polyvinyl alcohol with cellulose nanocrystals, coupled with a bioinspired strong dicarboxylic acid crosslinker namely ethanedioic acid. Results shown that both noncrosslinked and crosslinked biocomposites were able to degrade and the bacteria found responsible were Bacillus cereus strain CCM 2010 and Bacillus cereus strain ATCC 14579.